Analisis Buku Teks Bahasa Sunda Kelas XI Antara KIKD Dengan Sajian Materi Dalam Kurikulum 2013 Revisi 2017 Untuk Kondisi Khusus (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2022)
This research is motivated by the suitability and incompatibility between the contents of the textbook and the curriculum. The purpose of this study was to analyze and describe the relevance of the material presented in the Rancage Diajar Sundanese Language (RDBS) textbook for SMA/SMK/MA/MAK class XI and KIKD, which consists of the relevance of the subject, the structure of the material, and the depth of the material. The method used for this research is a qualitative descriptive method using a checklist technique. The data source of this research is the RDBS textbook for SMA/SMK/MA/MAK class XI which consists of 8 chapters. The results of this study can be described as follows: first, the subjects in class XI are generally relevant and included in the good category, namely 96.90%. Second, the material structure in class XI is in the sufficient category, which is 71.80%. Third, the depth of material in XI is in the sufficient category, which is 68.75%. Based on the results of the study, it can be concluded that the relevance of the material presented in the Rancage Diajar Sundanese Language (RDBS) textbook for SMA/SMK/MA/MAK class XI and KIKD, with respect to the subject matter in the good category, the structure of the material in the sufficient category, and the depth of the material. into the sufficient category.